Analisis dan Perancangan Sistem Pembelajaran Menggunakan Moodle - Tirsa Julianti Saruan; Arnold Horalto Umboh (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2023)
Education currently plays an important role in educating the nation's children, because they will later become the golden generation of this nation. Therefore the world of education must continue to evolve with the times and accept change. Learning activities in schools are required to study from home or be carried out boldly. Case studies in research at smk n 3 tondano, the learning system at smk n 3 tondano uses a learning system provided by the government. There were many deficiencies, so a learning system design using moodle was proposed, the learning system contained grades, absence information, exam schedule information and announcements regarding activities held by the school. The purpose of this study is to analyze the constraints of the learning system and the use of existing information and to design a website-based application that can be accessed at any time. Later this research is useful for improving the quality of technology-based education. Based on the existing problems, researchers will analyze the use of learning information systems using moodle to be a solution to existing problems. Analysis of utilization of learning information systems using moodle, you can find out the achievement of learning using moodle. Based on the results of the study it was concluded that the learning information system using moodle is very good at carrying out learning activities boldly.